Implementasi Metode Pendidikan Akhlak Imam Al-Ghazali dalam Peningkatan Perilaku Positif Siswa di MTsS Pesantren Darul Ulum Tigo Jangko Lintau Buo - Efendi, Fauzi Sastra; Rifauzi, Ahmad (TSAQOFAH, 2025)
This study aims to explore the implementation of Imam Al-Ghazali’s moral education methods in shaping and enhancing positive student behavior at MTsS Pesantren Darul Ulum Tigo Jangko, Lintau Buo. Employing a qualitative approach with a case study design, data were collected through in-depth interviews with teachers and students, observations of learning activities, and documentation. The findings indicate that Al-Ghazali’s methods, comprising habituation, role modeling, advice (mau‘izhah), self-monitoring (muraqabah), and introspection (muhasabah) are systematically applied in both classroom learning and daily life within the pesantren environment. The implementation of these methods positively contributes to students’ character formation, particularly in terms of discipline, responsibility, honesty, and politeness. The success of this implementation is supported by the active role of educators as role models, a supportive pesantren environment, and continuous moral guidance. The study concludes that Al-Ghazali’s principles of moral education are highly relevant for application in contemporary Islamic education systems as an effective strategy for nurturing morally and spiritually outstanding generations.